La fin de la guerre froide et les États membres du Conseil de l'Europe - Gelin, Evelyne (Études internationales, 1995)
Although the entry of Central Europe's new democracies into the Council of Europe proceeded rapidly and met little resistance, the Soviet federation's breakup has provided an opportunity to specify the criteria for admission to this organization. In regard to new candidacies for membership, it is worth recalling that member states must be sovereign states that respect fundamental rights and freedoms. Here, we have states whose independence was open to dispute, lying at the outermost limits of Europe, and seeking to free themselves from seventy-four years of "socialist democracy". This being the case, the Council of Europe must arbitrate between the particularises of its status, the necessities of diplomacy, and its willingness to open it self up.